A Clinical and Confocal Microscopic Comparison of Transepithelial PRK and LASEK for Myopia. (10th July 2014) - Korkmaz, Safak; Bilgihan, Kamil; Sul, Sabahattin; Hondur, Ahmet
Abstract : Purpose . To compare the clinical and confocal microscopic results of transepithelial PRK versus LASEK for correction of myopia. Materials and Methods . Twelve patients with myopia received transepithelial PRK in one eye and LASEK in the other. In transepithelial PRK-treated eyes, the corneal epithelium was removed with 40 microns of excimer laser ablation and in LASEK-treated eyes with 25-second application of 18% ethanol. Time to epithelial healing, ocular discomfort, uncorrected and best corrected visual acuities, manifest refraction, haze, greyscale value, and keratocyte apoptosis in confocal microscopy were recorded. Results . The mean time to epithelial healing was significantly longer after LASEK (4.00 ± 0.43 versus 3.17 ± 0.6 days). On day 1, ocular discomfort was significantly higher after transepithelial PRK. The grade of haze, keratocyte apoptosis, and greyscale value in confocal microscopy were significantly higher in transepithelial PRK-treated eyes at 1 month. All transepithelial PRK- and LASEK-treated eyes achieved 20/25 or better UCVA and were within ±1.00 D of emmetropia at final visits. Conclusions . Both transepithelial PRK and LASEK offer effective correction of myopia at 1 year. However, LASEK appeared to induce less discomfort and less intense wound healing in the early postoperative period.